Determination of the Optimal Thickness of the Floors of Multi-storey Concrete Structures with Modal Analysis - Botiş, Marius; Pleşcan, Costel (Springer International Publishing, 2022)
For multi-story concrete civil structures, the weight of the floors usually represents approximately 60% of the weight of the superstructure. For this reason, reducing the weight of the floors becomes important both for reducing the inertial mass of the structure and for reducing the reactive pressure of the ground on which the infrastructure rests. To optimize the thickness of the slabs, this article proposes a method based on modal analysis that allows establishing the thickness of the slabs by limiting the eigenvalue (period) in mode 1 at T = 0.2 s.